Penyuluhan Mengenal Strategi Pemasaran yang Efektif bagi Pemula di Panti Asuhan Putri Aisyiyah Pekanbaru - Setiawati; Refni Sukmadewi (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
This community service aims to introduce effective marketing strategies to novice users, namely the girls at the Putri Aisyiyah Orphanage Pekanbaru as partners. The problem faced by partners is increasing knowledge in implementing effective marketing strategies as beginners who can later become producers who succeed in creating consumer interest in a product in the business to be run. Of course, there is great hope that the business will grow. The method used is lecture and discussion (question and answer). With this method, the service team provides an explanation of effective marketing strategy materials and a few easy and practical examples they can do in developing the business they will run. In addition, the service team also provided success stories of business actors who started small businesses. Based on the results of this service activity in the form of counseling, it can be stated that this service activity was successfully carried out by enthusiastically listening to the material provided and being active in the discussion. From these results it can be seen that participants understand this material as knowledge that can be used to add to the marketing of a product from the business that will be run. Keywords: Beginner, Marketing Strategy, Knowledge